Agreement of variables selection and program development for data collection in thai intensive care unit by delphi method - Chittawatanarat K. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: The objective of this study was to determine the data collection variables and program for Thai intensive care units (ICU) as well as to obtain agreement using the modified Delphi method. Material and Method: The variables for program development were modified from the THAI-SICU study case record form. The first open discussion on the prototype was performed in a program development workshop. After revision, the stakeholder agreement was performed by modified Delphi method on the final browser program. All the categorical variable details were scored by a rating scale at five levels. The agreement level was defined as the median score at of least four and the interquartile range (IQR) up to two. Results: During June to September 2015, a total of 20 questionnaires from invited intensive care unit (ICU) expert stakeholders were returned (11 from physicians or surgeons, and 9 from critical care nurses). All of the seven parts of the variable groups, including: 1) patient characteristics, 2) diagnosis, 3) adverse events, 4) detail of operation in surgical cases, 5) ICU intervention, 6) discharge, and 7) summarized report, were agreed upon as the preset criteria (Median > 4 and IQR < 2). Conclusion: The selected variables in seven parts of the variable group via browser system were widely agreed upon from stake holders in Thai ICUs.